2021
DOI: 10.1021/acs.jmedchem.1c00370
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of o-(Biphenyl-3-ylmethoxy)nitrophenyl Derivatives as PD-1/PD-L1 Inhibitors with Potent Anticancer Efficacy In Vivo

Abstract: Two series of novel o-(biphenyl-3-ylmethoxy)­nitrophenyl compounds (A1–31 and B1–17) were designed as programmed cell death protein 1 (PD-1)/PD-ligand 1 (PD-L1) inhibitors. All compounds showed significant inhibitory activity with IC50 values ranging from 2.7 to 87.4 nM except compound A17, and compound B2 displayed the best activity. Further experiments showed that B2 bound to the PD-L1 protein without obvious toxicity in Lewis lung carcinoma (LLC) cells. Furthermore, B2 significantly promoted interferon-gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…As shown in Table , by incorporating the difluoromethyleneoxy motif as an unusual bioisosteric replacement of the methoxy linkage and retaining other structural components intact, compound 25 displayed an IC 50 of 31.87 nM against the PD-1/PD-L1 interaction, which is slightly more potent than reference compound 2 (IC 50 = 48.2 nM). A quick screening of a small set of alkylamino alcohols/acids widely used in the literature ,, as the solvent interaction structural motif indicated that all the resulting compounds 26–28 retained high inhibitory activity against the PD-1/PD-L1 interaction, and compound 28 bearing a 2-amino-2-methylpropane-1,3-diol component showed more increased potency with an IC 50 value of 16.31 nM. Keeping the 2-amino-2-methylpropane-1,3-diol component intact and changing the substitution pattern of the central tetra-substituted phenyl ring from 3-methyl to the 4-chloro pattern led to compound 29 , showing a much improved potency with an IC 50 value of 5.93 nM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table , by incorporating the difluoromethyleneoxy motif as an unusual bioisosteric replacement of the methoxy linkage and retaining other structural components intact, compound 25 displayed an IC 50 of 31.87 nM against the PD-1/PD-L1 interaction, which is slightly more potent than reference compound 2 (IC 50 = 48.2 nM). A quick screening of a small set of alkylamino alcohols/acids widely used in the literature ,, as the solvent interaction structural motif indicated that all the resulting compounds 26–28 retained high inhibitory activity against the PD-1/PD-L1 interaction, and compound 28 bearing a 2-amino-2-methylpropane-1,3-diol component showed more increased potency with an IC 50 value of 16.31 nM. Keeping the 2-amino-2-methylpropane-1,3-diol component intact and changing the substitution pattern of the central tetra-substituted phenyl ring from 3-methyl to the 4-chloro pattern led to compound 29 , showing a much improved potency with an IC 50 value of 5.93 nM.…”
Section: Resultsmentioning
confidence: 99%
“…By taking advantage of the interaction profile of the biaryl core component, Hu and Holak reported a series of C 2 -symmetric 2,2′-dimethyl-3,3′-bis­(aryloxymethyl)-1,1′-biphenyl analogues, among which compound 3 (Figure ) exhibited an IC 50 value of 3.0 nM in the HTRF assay . A ring fusion strategy was conducted by Gong’s and Wang’s groups, and the representative compounds [1,2,4]­triazolo­[4,3-α]­pyridine 4 and indolin 5 showed IC 50 values of 92.3 and 11.2 nM, respectively. , More recently, Lai and co-workers reported a series of nitrophenyl derivatives, and compound 6 showed an IC 50 value of 2.7 nM . In addition, optimization of the methoxy (−CH 2 O−) linker was conducted by two groups.…”
Section: Introductionmentioning
confidence: 99%
“…In a peripheral blood mononuclear cell (PBMC)-based assay, BMS-202, one of the early biphenyl compounds with poor cellular activity in the NFAT reporter assay ( 53 ), showed significant rescue of interferon gamma (IFN-γ) secretion inhibited by PD-L1 at a lower concentration (100 nM) similar to another biphenyl compound, Compound 58 ( 54 ). The biphenyl compound B2 has been shown to induce IFN-γ secretion from the lymph node T cells co-cultured with LLC cells and rescue the inhibition of IFN-γ secretion from PD-L1 of PBMC treated with anti-CD3/anti-CD28, with a potency similar to that observed in biochemical assay for the disruption of PD-1/PD-L1 interaction ( 56 ). During the discovery of amino-acid-inspired interface mimic CA-170, a PBMC-based function assay monitoring the rescue of T cells from the inhibitory activity of PD-L1 in inducing proliferation and cytokine secretion was extensively used.…”
Section: Analysis Of Functionalitymentioning
confidence: 89%
“…A number of reports are also emerging recently from the industry and academia using the privileged structure of biphenyl-containing compounds and their various derivatives to improvise the druggability of the molecules. This includes scaffold based on nicotinyl alcohol ether derivative ( 45 – 47 ), resorcinol dibenzyl ether ( 48 ), 4-phenylindoline derivatives ( 49 ), combining two privileged scaffolds such as biphenyl backbone structure and 2-amino-pyrimidine structure ( 50 ), biphenyl-4-carboxamide derivatives ( 51 ), incorporating taurine moieties ( 52 ), 1-methyl-1H-pyrazolo[4,3-b] pyridine derivatives ( 53 ), replacing the linker connecting aryl group and biaryl core with a novel amine linker ( 54 ), a series of novel biphenyl pyridines derivatives lacking linker ( 55 ), biphenyl methyl nitrophenyl core unit ( 56 ), and terphenyl scaffold derived from the rigidified biphenyl inspired structure ( 57 ). Representative structures of the compounds disclosed are presented in Figure 3 .…”
Section: Two Major Classes Of Small Molecules Targeting Pd1-pd-l1 Axismentioning
confidence: 99%
See 1 more Smart Citation